2018
DOI: 10.1007/s11095-018-2414-5
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Loaded Copper Oleate PEGylated Liposome Combined with Disulfiram for Improving Synergistic Antitumor Effect In Vivo

Abstract: The Cu(OI)-L was suitable to be employed in combination with disulfiram for tumor treatment and can also open up opportunities for targeted delivery of copper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…These results are also supported by a recent study using DSPE-PEG 2000 -based PEGylated copper oleate liposome (Cu(OI)2-L) for targeted delivery in cancer. Pharmacokinetic studies demonstrated that Cu(OI)2-L had a prolonged circulation time compared to that of injected copper oleate solution [46]. However, no stability study results in serum were shown and the feasibility (and compatibility) of combining DS with Cu +2 in the same dosage form should be investigated in depth.…”
Section: Resultsmentioning
confidence: 99%
“…These results are also supported by a recent study using DSPE-PEG 2000 -based PEGylated copper oleate liposome (Cu(OI)2-L) for targeted delivery in cancer. Pharmacokinetic studies demonstrated that Cu(OI)2-L had a prolonged circulation time compared to that of injected copper oleate solution [46]. However, no stability study results in serum were shown and the feasibility (and compatibility) of combining DS with Cu +2 in the same dosage form should be investigated in depth.…”
Section: Resultsmentioning
confidence: 99%
“…A major barrier towards the development of [Cu(S 2 CNEt 2 ) 2 ] and related complexes derived from non-polar secondary amines is their extremely poor water solubility (<1 mg mL −1 ). There are a number of possible ways around this, one being to co-deliver disulfiram and Cu(II) such that they react and generate [Cu(S 2 CNEt 2 ) 2 ] within the tumour microenvironment [268][269][270]. This can be done in a number of ways, the most common being the incorporation of disulfiram and Cu(II) into a polymeric nanoparticle, for example as reported by Pu and co-workers who used a poly(ethylene glycol) (PEG)-b-poly(ester carbonate) (PEC) composite [270].…”
Section: Anticancer Agentsmentioning
confidence: 99%
“…chelate with copper ion [17,18,20]. For example, DSF/Cu selectively killed human breast cancer cell MDA-MB-231 and lymphocytic leukemia cells in the blood system, but it produced little impact on MCF-10A, normal breast epithelial cells, and normal lymphocytes [11,[21][22][23].…”
Section: Open Accessmentioning
confidence: 99%
“…Several mechanisms of disulfiram cytotoxicity were reported, including irreversible inhibition of aldehyde dehydrogenase (ALDH) and the P-glycoprotein (P-gp) multidrug efflux pump [11,12], superoxide dismutase (SOD) [13,14] and activating nuclear factor-κB (NF-κB) [15,16]. The ability of DSF to chelate divalent cations, such as copper and zinc, also improves its biological activity against tumors [17,18]. Copper plays a critical part in oxidation-reduction reactions and the generation of reactive oxygen species (ROS) in both tumor and normal cell.…”
Section: Introductionmentioning
confidence: 99%